EKSISTENSI TRADISI UPACARA PERANG SAMBUK DALAM PENGUATAN PENDIDIKAN KEAGAMAAN DI DESA ADAT BUDUK KECAMATAN MENGWI KABUPATEN BADUNG - Ni putu ayu candra, Dewi; Lestawi, I Nengah; Wulandari, Ida Ayu Gde (UHN IGB Sugriwa Denpasar, 2024)
ASBTRACT ​The tradition of the Sambuk War Ceremony in the Buduk Traditional Village, Mengwi District, Badung Regency is a sacred ritual that is included in an earlier ancestral heritage that contains high noble values ​​in life. This tradition is carried out once a year, namely on the day of tilem kesanga. The formulation of the problems that will be discussed include; (1) How is the existence of the Sambuk War Ceremony Tradition in the Buduk Traditional Village, Mengwi District, Badung Regency? (2) What is the function of the Sambuk War Tradition Ceremony for the people of Buduk Traditional Village, Mengwi District, Badung Regency? (3) What are Hindu religious education values ​​are contained in the Sambuk War Ceremony Tradition in Buduk Traditional Village, Mengwi District, Badung Regency? ​This research uses religious theory, existential theory, structural functionalism theory, and value theory. The technique of determining purposive informants is where the person who becomes the informant is a figure from the community. The data analysis technique is done by sorting the data obtained through interviews and field observations to seek scientific validation of the analyzed data, so as to produce a logical conclusion that can be accounted for. ​The results obtained in the research entitled The Existence of the Sambuk War Tradition Ceremony in Strengthening Religious Education in the Buduk Traditional Village, Mengwi District, Badung Regency are; (1) Implementation of the Sambuk War TraditionCeremony which is carried out on the day of Tilem Kesanga, before the Tradition is carried out. The first series of ceremonies carried out are the Mekiis and Mecaru ceremonies. After performing the ceremony, the Sambuk War Ceremony Tradition can be carried out. (2) There are three functions of the Sambuk War Ceremony, namely the religious function, the harmony function, and the unity function. (3) Hindu religious education values ​​contained in the Sambuk War Ceremony Tradition are divine values, ethical values, aesthetic values, social values ​​and cultural values Keywords: Existence of Sambuk War Ceremony Tradition, Hindu religious education